Collection Development in NISTADS Library - Bali, Anita (DESIDOC Journal of Library & Information Technology, 2003)
This paper describes the collection development program in National lnstitute of Science, Technology and Development Studies (NISTADS) library. The library had good financial support but it could not meet all the requirement of its user community due to the exponential growth of literature, rising price of books and periodicals and shortage of space. An appropriate collection development plan was developed by resource sharing with outside libraries and making use of available information technology. http://dx.doi.org/10.14429/dbit.17.2.3330